Studi Korelasi Pengetahuan Gizi dan Praktek Gizi Seimbang Dengan Status Gizi Remaja Putri - Wijayanti Wijayanti; Rusiana Sri Haryanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Adolescent girls with good nutritional status are one of the efforts to prevent stunting. Indonesia is faced with three burdens of nutritional problems, namely the high prevalence of stunting, wasting, obesity and anemia. Good nutritional status can be realized if balanced nutrition practices are carried out properly. The practice of balanced nutrition is a response to balanced nutrition knowledge in consuming balanced foods and behaving in a healthy life The purpose of the .to determine the correlation of nutritional knowledge and and practice of balanced nutrition with the nutritional status of adolescent girls. survey research with Cross Sectional approach. The research was conducted at MAN 1 Surakarta, January – June 2023. The number of samples seemed to be 30 people. Sampling using purposive sampling. Data collection using questionnaires, Height measurement (TB) with Microtoise staturmeter and Weight measurement (BB) with manual weight scale. The statistical test was performed univariately, bivariately with Chi Square test (ɑ = 0.05). A significant relationship between the level of nutritional knowledge and balanced nutrition practices (r: 0.434), a significant relationship between the level of nutritional knowledge and nutritional status (r: 0.596), a significant relationship between balanced nutrition practices and nutritional status (r: 0.486). There is a significant relationship between the level of nutritional knowledge, balanced nutrition practices and nutritional status with moderate closeness